TINJAUAN YURIDIS TERHADAP PERKAWINAN ANAK DI BAWAH UMUR BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI WILAYAH KECAMATAN CAKUNG JAKARTA TIMUR - Virza Syatri; Mugiati (Constitutum: Jurnal Ilmiah Hukum, 2024)
Legally, child marriage is considered invalid because it violates the regulations regarding the minimum age limit for marriage for men and women, including in Cakung District, East Jakarta. This study discusses the factors that cause child marriage and the role of the government in preventing child marriage in Cakung District, East Jakarta. The method used in this study is an empirical normative legal approach. The results of the study indicate that the factors that influence child marriage in Cakung District include parental/family factors, economic factors, individual willingness, media influence, and marriage due to accidents. To reduce the number of child marriages in Cakung District, the government has implemented several policies, including conducting socialization about child marriage in schools every six months, family planning socialization in villages or local health centers targeting parents and children, and distributing brochures in densely populated areas to invite parents and children to prevent child marriage.